Navigating an evolving microbial landscape: emerging antimicrobial resistance trends and precision stewardship in Tianjin tertiary hospitals (2021–2023) - Wan, Yong-li; Han, Tao; Sun, Qiang; Wang, Donghao; Li, Jun; Wang, Li-jie; Peng, Min; Li, Yin; Feng, Qing-guo; Liu, Chun-guang; Xu, Jie; Bao, Bin; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo evaluate microbial distribution and antimicrobial resistance (AMR) patterns in clinical isolates from 13 tertiary hospitals and one secondary hospital in Tianjin (2021–2023) to inform precision-driven antimicrobial stewardship and infection control interventions.MethodsIn this retrospective, multicenter study, we collected routine diagnostic specimens—including sputum, fecal samples, secretions, blood, and drainage fluids. Data were processed per standardized protocols (CARSS, CHINET) and interpreted using current CLSI-M100 breakpoints. Statistical analyses were performed with SPSS 20.0 (significance set at two‐tailed P < 0.05).ResultsSputum specimens increased from 39.1% to 43.0%, while urine samples and secretions declined. Klebsiella pneumoniae prevalence rose from 18.3% to 20.3%, whereas Escherichia coli remained stable. E. coli maintained excellent susceptibility to carbapenems and amikacin (≤2% resistance); notably, ceftazidime/avibactam resistance declined from 7.2% to 3.4% (P = 0.005) amid a significant increase in cefepime resistance (24.4% to 29.6%, P < 0.001). K. pneumoniae exhibited parallel trends, with escalating resistance to β-lactam/β-lactamase inhibitor agents. In Pseudomonas aeruginosa, aminoglycoside, and carbapenem profiles remained stable, while ceftazidime/avibactam sensitivity markedly improved, suggesting shifts in underlying resistance mechanisms. Acinetobacter baumannii showed enhanced susceptibility to aminoglycosides, β-lactam inhibitors, and fluoroquinolones; however, carbapenem-resistant isolates continued to exhibit near-universal resistance. Among gram-positive pathogens, methicillin-resistant Staphylococcus aureus sustained near-universal β-lactam resistance with improved rifampicin sensitivity, while glycopeptides and linezolid remained fully active. Enterococcus faecalis demonstrated reduced ampicillin resistance, contrasting with E. faecium’s near-pan-resistance to β-lactams and fluoroquinolones.ConclusionEvolving, species-specific AMR patterns in Tianjin hospitals highlight the urgent need for real-time, regionally stratified surveillance and molecularly informed stewardship strategies to guide targeted antimicrobial interventions and improve clinical outcomes.